"A Trespass against the Whole Species": Universal Crime and Sovereign Founding in John Locke's Second Treatise of Government. (August 2018) - Graf, Sinja
This essay theorizes how the enforcement of universal norms contributes to the solidification of sovereign rule. It does so by analyzing John Locke's argument for the founding of the commonwealth as it emerges from his notion of universal crime in the Second Treatise of Government . Previous studies of punishment in the state of nature have not accounted for Locke's notion of universal crime which pivots on the role of mankind as the subject of natural law. I argue that the dilemmas specific to enforcing the natural law against "trespasses against the whole species" drive the founding of sovereign government. Reconstructing Locke's argument on private property in light of universal criminality, the essay shows how the introduction of money in the state of nature destabilizes the normative relationship between the self and humanity. Accordingly, the failures of enforcing the natural law require the partitioning of mankind into separate peoples under distinct sovereign governments. This analysis theorizes the creation of sovereign rule as part of the political productivity of Locke's notion of universal crime and reflects on an explicitly political, rather than normative, theory of "humanity."